Assessment of Non-Tariff Measures (NTMs) and their Impacts on International Trade and Competitiveness of Thailand and Lao PDR - PHONVISAY, Alay (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
Non-tariff measures (NTMs) have increasingly become an essential tool for countries to regulate trade in the global marketplace. According to recent data, the use of NTMs worldwide has risen sharply in the past decade, there are more than 2.5 million product NTMs in the world and more than 78% of world trade is subject to at least one NTM. Over the 537 NTMs of Lao PDR imposed from 1996 to 2018, 532 NTMs affect Thailand, and 9 NTMs exclusively affect Thailand. Thailand imposes 66 NTMs exclusively on Lao PDR. This paper aims to assess NTMs and their impact on the international trade and competitiveness of Thailand and Lao PDR. The Lao PDR’s NTMs imposed exclusively on Thailand consist only of technical measures for import and export. On the other hand, Thailand's NTMs have been affecting Laos' exports to Thailand, which is its largest trading partner in the ASEAN region. Thailand's NTMs include TBTs and SPS measures, among others, which are affecting the trade relations between the two countries. NTMs such as SPS and TBT measures are remaining challenges for Lao exporters due to their internal capacity. To enhance the oversight and implementation of SPS and TBT measures in Lao PDR, international development organizations should be requested to provide short-term technical assistance and funding for various activities.